Role of the Behavioral Integrity of the Leader in Building the Core Competencies of Human Resources: Analytical Research Of Sample Opinions Of Health Staffs in Private Hospitals - محمود فهد الدليمي; حسين حريجة الحسناوي; رؤى صالح مهدي (Iraqi Journal for Administrative Sciences, 2024)
The research objective of main is to determine the nature of the relationship between the behavioral integrity of the leader and the core competencies of the human resources at the level of a sample of health staff in some private hospitals, based on a basic problem identified by several questions including the extent of understanding the influential relationships between the variables at the field level. In measuring the behavioral integrity of the leader in five sub-dimensions (Consistency, Lawful, Ethical and Moral Purpose, Stand for something ; and Identity), while measuring the core competencies of human resources in three sub-dimensions (Knowledge, Skill, , and Attitudes ). A sample of medical and nursing staff was selected in some private hospitals (Specialist Al-Kafil Hospital, Al Abidine Zine Hospital, Al-Safir Hospital and private Al-Abbas Hospital) as a sample of the number of (182) individuals distributed by (98) doctors and (84) nurses. The results of the statistical analysis showed the moral influence of the behavioral integrity of the leader in building the core competencies of human resources. The results showed progress for the dimension of consistency and legitimacy and it after the ethical and moral purpose and then after Stand for something and finally the identity in terms of the impact on building the core competencies of the human resources